명태, 폐계가슴살 및 기계발골계육을 활용한 수리미의 품질 특성 - 진상근; 김일석; 양한술; 최영준; 김병균[한성식품; Jin, S.K; Kim, I.S; Yang, H.S; Choi, Y.J; Kim, B.G (Journal of animal science and technology, 2007)
This study was carried out to compare the physico-chemical and sensory characteristics of surimi manufactured by four different materials. We prepared surimi from alaska pollack, as the control, by washing method. The different treatments of surimi were manufactured by pH 11.0 adjustments with barren hen breast meat(T1), commercial mechanically deboned chicken meat(MDCM)-S. Co. (T2)and MDCM- J. Co.(T3). Whiteness, cohesiveness and overall acceptability were significantly higher but gumminess, chewiness and gel characteristics were significantly lower in control than other surimi samples(P<0.05). Lightness, brittleness, deformation, jelly strength and flavor were higher but texture properties and folding test of T1 were lower than those of other treatments(P<0.05). Texture properties, shear force and gel characteristics were higher, while deformation and acceptability of T2 were lower than those of other treatments(P<0.05). On the other hand, cohesiveness was higher, and lightness and whiteness were lower in T3 than those of other treatments(P<0.05). Correlation coefficients(>0.9) among texture properties and gel characteristics was positive, while negative among surface surimi colors(P<0.05). The content of crude protein, cohesiveness and gel characteristics indicated that the acceptable surimi can be made is replaced barren hen breast meat and MDCM. 수리미 원료육의 특성을 분석하기 위하여 폐계가슴살(T1), 기계발골계육인 S사 MDCM(T2) 및 J사 MDCM(T3)을 활용하여 pH 11.0의 알칼리 조절법으로 수리미를 제조한 후 품질 특성을 비교한 결과 명태연육을 활용한 수리미인 대조구는 다른 처리구들에 비해 백색도, 응집성, 관능평가의 기호도가 높은 장점을 나타낸 반면 검성, 씹힘성 및 겔 특성이 낮은 단점을 나타내었다. T1은 다른 처리구들에 비해 명도, 표면경도, 변형값, 젤리강도 및 관능평가의 향이 높은 장점을 나타낸 반면 조직감 및 접기실험 결과가 낮게 나타났다. T2는 다른 처리구들에 비해 조직감, 전단가 및 겔 특성이 높은 반면 변형값, 관능평가의 기호도가 낮고, 황색도가 높은 단점을 나타내었다. 또한 T3의 경우 다른 처리구들에 비해 응집성이 가장 높았으며, 적색도가 높고, 명도 및 백색도 낮은 단점을 나타내었다. 결론적으로 원료육의 차이에 따른 수리미의 품질 특성을 비교한 결과 폐계가슴살을 활용한 T1에서 높은 단백질 함량과 낮은 지방 함량을 보여 수리미 원료로서의 활용도가 높을 것으로 판단된다. 또한 수리미 주요 겔 특성인 변형값과 응집성을 중심으로 볼 때 명태연육을 대체할 수 있는 수리미 원료육으로 T1과 T3가 뛰어난 것으로 나타났다. 그러나 T1과는 달리 MDCM(T2 및 T3)은 적색도가 높고 백색도가 낮아 수리미 제조시 외관적 제품 특성에 부정적인 영향을 미칠 뿐만 아니라 기호도에서 낮은 점수를 획득하여 이에 대한 추가 연구가 필요할 것이라 판단된다.